Early maladaptive schemas and symptoms of depression in people cared for in a hospital specialized in mental health - Barreda Sánchez-Pachas, Dennys Vanessa (2021)
The objective of this research was to establish the difference in the magnitude of Early Maladaptive Schemas (EMT) in clinical samples, 136 participants with and 135 without symptoms of depression, as well as to evaluate the association between symptoms of depression and EMT. The sampling was intentional non-probabilistic, with 125 men and 146 women, treated in a hospital specialized in mental health, prior to diagnosis. The instruments used were: Young's Schema Questionnaire-Brief Version (YSQ-S3) and the Beck Depression Inventory II (BDI-II). The results showed statistically significant differences between both groups (p <.05) in the five dimensions and their respective schemas (18), the size of these differences ranged from small to large, with rbis values between .23 to .64; evidencing that the schemas are presented in greater magnitude in the sample with symptoms of depression. The statistically significant positive association between the five dimensions, 17 EMT and the symptoms of depression was confirmed, the strength of the association was moderate in two dimensions and two EMT and the minimum necessary to present interdependence between the variables in three dimensions and 15 EMT with coefficients of determination ranging from .044 to .383; observing that the schemas are more severe as soon as more intense symptoms of depression appear; However, this association is not fulfilled in the Unrelenting standards schema, since considering inaccessible limits requires a high concentration and continuous demand, which is not consistent with the symptoms of depression.